Characterizing the respiratory-induced mechanical stimulation at the maxillary sinus floor following sinus augmentation by computational fluid dynamics - Li, Qing; Wang, Zhongyu; Wang, Chao; Wang, Hom-Lay (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The relationship between maxillary sinus pneumatization and the respiratory-induced fluid mechanics remains unclear. The purpose of this study was to simulate and measure the respiratory-induced mechanical stimulation at the sinus floor under different respiratory conditions and to investigate its potential effect on the elevated sinus following sinus-lifting procedures. Methods: The nasal airway together with bilateral maxillary sinuses of the selected patient were segmented and digitally modelled from computed tomographic image. The sinus floors of the models were elevated by simulated sinus augmentations using computed-aid design. The numerical simulations of sinus fluid motion at different respiratory conditions were performed using a computational fluid dynamics (CFD) algorithm. Sinus wall shear stress and static pressure on the pre-surgical and altered sinus floor were examined and quantitatively compared. Results: Streamlines with minimum airflow velocity were visualized in the sinus. The sinus floor pressure and the wall shear stress increased with the elevated inlet flow rate, but the magnitude of these mechanical stimulations remained at a negligible level. The surgical technique and elevated height had no significant influence on the wall pressure and the fluid mechanics. Conclusion: This study shows that respiratory induced mechanical stimulation in the sinus floor is negligible before and after sinus augmentation.